Interpreting Diachronic Size Variation in Prehistoric Central Asian Cereal Grains - Motuzaite Matuzeviciute, Giedre; Mir-Makhamad, Basira; Spengler, Robert N. (Frontiers in Ecology and Evolution, 2021)
The morphology of ancient cereal grains in Central Asia has been heavily discussed as an indicator of specific genetic variants, which are often linked to cultural factors or distinct routes of dispersal. In this paper, we present the largest currently existing database of barley (n=631) and wheat (n=349) measurements from Central Asia, obtained from two different periods at the same Chap site (ca. 3500 to 1000 BC), located in the Tien Shan Mountains of Kyrgyzstan at 2,000 masl. The site is situated at the highest elevation ecocline for successful cereal cultivation and is, therefore, highly susceptible to minor climatic fluctuations that could force gradients up or down in the foothills. We contrast the Chap data with measurements from other 2nd and 1st millennia BC sites in the region. An evident increase in average size over time is likely due to the evolution of larger grains, or the introduction of larger variants from elsewhere. Additionally, site- or region-specific variation is noted, and we discuss potential influences for the formation of genetic varieties, including possible pleiotropic linkages and/or developmental responses to external factors, such as environmental fluctuations, climate, irrigation inputs, soil nutrients, pathologies, and seasonality. External factors acting on developmental or acclamatory responses in plants can be either natural or cultural. We argue that the study of long-term changes in grain morphology on the edges of crop growing ranges can be informative regarding cultural and environmental constraints in the past.